Hematopoietic transcription factors and differential cofactor binding regulate PRKACB isoform expression - Lausen, Olga Nikolaevna; Müller-Tidow, Carsten (OncoTarget, 2017)
Hematopoietic differentiation is controlled by key transcription factors, which regulate stem cell functions and differentiation. TAL1 is a central transcription factor for hematopoietic stem cell development in the embryo and for gene regulation during erythroid/megakaryocytic differentiation. Knowledge of the target genes controlled by a given transcription factor is important to understand its contribution to normal development and disease. To uncover direct target genes of TAL1 we used high affinity streptavidin/biotin-based chromatin precipitation (Strep-CP) followed by Strep-CP on ChIP analysis using ChIP promoter arrays. We identified 451 TAL1 target genes in K562 cells. Furthermore, we analysed the regulation of one of these genes, the catalytic subunit beta of protein kinase A (PRKACB), during megakaryopoiesis of K562 and primary human CD34+ stem cell/progenitor cells. We found that TAL1 together with hematopoietic transcription factors RUNX1 and GATA1 binds to the promoter of the isoform 3 of PRKACB (Cβ3). During megakaryocytic differentiation a coactivator complex on the Cβ3 promoter, which includes WDR5 and p300, is replaced with a corepressor complex. In this manner, activating chromatin modifications are removed and expression of the PRKACB-Cβ3 isoform during megakaryocytic differentiation is reduced. Our data uncover a role of the TAL1 complex in controlling differential isoform expression of PRKACB. These results reveal a novel function of TAL1, RUNX1 and GATA1 in the transcriptional control of protein kinase A activity, with implications for cellular signalling control during differentiation and disease.